Epigenetic Input Dictates the Threshold of Targeting of the Integrin-Dependent Pathway in Non-small Cell Lung Cancer - Zhang, Yang; Cheng, Kai; Xu, Bingwei; Shi, Junfeng; Qiang, Jun; Shi, Shujin; Yi, Yuanqin; Li, Hongxia; Jin, Tengchuan; Guo, Ruihua; Wu, Yadi; Liu, Zeyi; et al. (Frontiers in Cell and Developmental Biology, 2020)
With increasing link of integrin/FAK-dependent signaling to NSCLC malignancy, we investigated therapeutic potential of targeting this adhesion receptor-mediated pathway. Our analysis of the TCGA cohort showed that a subset of pro-tumorigenic integrins, including α1β1, α2β1, α3β1, α5β1and α6β4, were frequently amplified or upregulated at genomic or mRNA level in KRAS or EGFR mutation/overexpression-enriched adenocarcinomas. These alterations appeared complimentary and correlated with poor patient survival, regardless of KRAS mutation-coupled αv integrins (p <0.0072). Since the integrin/FAK-dependent signaling is tightly coupled with normal human physiology, we sought for a synthetic lethal-type targeting with VS-6063, a chemical inhibitor of integrin-mediated FAK activity, and A549 cells, which carry KRAS mutation and EGFR overexpression. Our screening analysis revealed that JQ1 and IBET-762 -inhibitors of epigenetic reader BRD4, and LBH589 -a pan inhibitor of histone deacetylases (HDACs), exhibited a synergy with VS-6063 in terms of mitigating tumor cell viability. This epigenetic link was corroborated by strong effects of additional inhibitors and RNAi-mediated knockdown of FAK and BRD4 or its downstream effector c-Myc. Intriguingly, low doses of JQ1 (≤ 0.5µM) markedly escalated efficacy of VS-6063 across a panel of 10 NSCLC cell lines. This catalyst-like effect was in line with our pathway analysis of the TCGA cohort, where c-Myc falls downstream of KRAS and EGFR oncogenes. Mechanistically, co-inhibiting the integrin-FAK and BRD4/c-Myc axes synergistically induced apoptotic cell death and DNA damage response, and impaired stemness-associated tumorsphere formation. These effects were accompanied by a marked inhibition of Akt-and p130Cas/Src-dependent signaling, but not Erk1/2 activity. Meanwhile, JQ1 alone or in combination with VS-6063 attenuated cellcell adhesion and extracellular matrix (ECM)-dependent cell spreading, reminiscent of phenotypic changes caused by malfunctional E-cadherin or integrins. Paradoxically, this phenotypic impact also coincided with downregulation of EMT-inducting transcription factor ZEB1 and Snail. Moreover, effect of the VS-6063/JQ1 combination was nearly equivalent to that of VS-6063 plus Carboplatin or Osimertinib in terms of cell apoptosis, DNA damage response, and suppression of c-Myc. Taken together, our results suggest that the integrin/FAK and BRD4/c-Myc axes cooperatively drive NSCLC virulence, and a cotargeting may serve as a new line of therapy capable of overcoming EGFR-or RAS/MEK/Erk1/2-driven malignancy.